THE INFLUENCE OF BRAND KNOWLEDGE IN CHOOSING HOSPITAL - Setyawati, Candra; Rochmah, Thinni Nurul (Universitas Airlangga, 2015)
ABSTRACT Brand knowledge is an information and public knowledge measurement related to consuming product. Low of care visit in clinical care of specialist dental health and hospital are 22% from maximum supply count each year, so it needs to analyze the decision of choosing Airlangga University Dental Health and Hospital based on brand knowledge. This study was an observational analytic, and based on the time, this study was cross-sectional study with stratified random sampling. There were 100 respondents that participated in this study. Statistical test used logistic regression. The result of this study indicated that there was no effectbetween brand awareness with the public desicion to visit Airlangga University Dental Health and Hospital (p=0,746) and also there was no effectbetween brand image with the public decision to visit Airlangga University Dental Health and Hospital (p=0,138). This study concluded that there was no effectof brand knowledge (that consists of brand awareness and brand image) toward the public decision in choosing Airlangga University Dental Health and Hospital. According to the result, Airlangga University Dental Health and Hospital should improve their medical service quality by advertising and dissemination of their medical service information. Keywords: brand awareness, brand image, brand knowledge, decision, hospital